Последний поклон: повесть (В. П. Астафьев) - Астафьев Виктор Петрович (1989)
Экземпляры: Селтинская районная библиотека (аб) (20191008) / Инвентарный номер: 142068 / Цена: / Авт.знак: А 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6